Annotated list of species of marine crustaceans (Decapoda and Stomatopoda) from Golfo Dulce, Costa Rica - Castro, Mauricio (1996)
The present study is an annotated list of the marine crustaceans (Decapoda and Stomatopoda) from Golfo Dulce, Costa Rica, collected during the RV Victor Hensen Cruise 1993-1994, at depths ranging from 20 to 260 m. Stomatopoda was represented by one family and two species. Decapoda was represented by 12 families and 21 species. Two new records for Costa Rica, Cancer johngarthi and Lysmata californica are reported. This increases the reported marine crustaceans of Golfo Dulce to three species of Stomatopoda and sixty-six of Decapoda (a complete checklist is included). A list of species reported in the literature from the gulf is also included.